Effects of decision making styles on entrepreneurship skills - Yener, Huseyin (Technium Social Sciences Journal, 2020)
Entrepreneurship usually has a highly ambiguous atmosphere, and so needs a variety of skills. This study explores the relationships between entrepreneurial skills and decision making styles. In the study relational screening model was used and the study group consisted of 30 students of a private university in Istanbul, Turkey. Two questionnaires which were a 25-item entrepreneurship questionnaire and a 22-item Melbourne decision making questionnaire applied to sample group. Descriptive statistics and all the other tests were conducted by using SPSS version 26 to examine the extent of involvement, significance, direction and degree of the relationships. The results indicated a positive low-level (r = 0.374) relationship between entrepreneurship skill and vigilance type of decision making style. Surprisingly, negative low level of relationships (r = -0.123 and r = -0.244, p <0.05) were found among entrepreneurship skills, hypervigilance and procrastination styles. No significant interaction with buck passing type of decision making style was found. It was found that parental education/job status and entrepreneurship history of family have no effect on entrepreneurship skills. This result supported the idea that entrepreneurship is a learnable skill rather than an innate skill. It is recommended to include active teaching programs for the development both of skills.